2006
DOI: 10.1192/bjp.bp.106.021386
|View full text |Cite
|
Sign up to set email alerts
|

Group cognitive-behavioural therapy for schizophrenia

Abstract: Although group cognitive-behavioural therapy may not be the optimum treatment method for reducing hallucinations and delusions, it may have important benefits, including feeling less negative about oneself and less hopeless for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…89,95,[103][104][105] These conclusions are largely consistent with the results of recent meta-analyses. [106][107][108] However, some studies have not found CBT to improve patient outcomes in these domains including hallucinations, 105 positive symptoms, [109][110][111][112] negative symptoms, [109][110][111][112] and social functioning. 98,109,110 The effects of CBT on depression, suicidality, hopelessness, illness insight, relapse, and rehospitalization have not been clearly established with only a small number of studies examining these outcomes.…”
Section: Supported Employmentmentioning
confidence: 99%
“…89,95,[103][104][105] These conclusions are largely consistent with the results of recent meta-analyses. [106][107][108] However, some studies have not found CBT to improve patient outcomes in these domains including hallucinations, 105 positive symptoms, [109][110][111][112] negative symptoms, [109][110][111][112] and social functioning. 98,109,110 The effects of CBT on depression, suicidality, hopelessness, illness insight, relapse, and rehospitalization have not been clearly established with only a small number of studies examining these outcomes.…”
Section: Supported Employmentmentioning
confidence: 99%
“…A number of influential research studies have demonstrated that patients with schizophrenia who are treated with CBT often experience a reduction in delusions, hallucinations, and negative symptoms that go beyond the results of pharmacotherapy alone. 24,25,35 CBT is partly based on the evidence that emotional processes, information processing deficits, reasoning, and appraisal biases contribute to the formation and maintenance of delusions and hallucinations, and partly on changing these processes through cognitive intervention. CBT has significant effects on brain functioning and other biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…47 Also, other authors have demonstrated that CBT contributed to significantly greater improvements in terms of verbal learning, psychomotor speed, and global cognitive functioning. 24,25,[48][49][50][51][52][53][54][55][56][57][58] Many of the studies that were reviewed have demonstrated the effectiveness of the CRT intervention. For example, Lindenmayer et al evaluated the feasibility and efficacy of a CRT program for improving cognitive and work functioning for intermediate-to longstay psychiatric inpatients.…”
Section: Monthsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Thus, part of the recovery process involves the challenges of remaining optimistic and fulfilling full potential and well-being. While there is clearly a strong evidence base for CBTP, including much of our own work, [36][37][38][39][40][41] research indicates that CBTP does not significantly reduce suicide behaviour; 42 thus, the development of CBT for suicide prevention is a priority. There are also other limitations with respect to the delivery of CBTP mentioned above, so alternative modes of delivery need to be explored.…”
Section: Introductionmentioning
confidence: 98%